Consentimiento sexual. Una propuesta de análisis feminista y sociológico - Moreno Standen, Claudia (El Colegio de México, 2024)
Sexual consent constitutes a fundamental ethical issue in contemporary societies, the challenges of which have been recently highlighted by global movements such as #MeToo. This article proposes a sociological and feminist approach that advocates for understanding consent within the framework of everyday sexual relations, gender and power dynamics, and social structures. It explores three dimensions: the social architectures that frame gender relations, the sexual narratives and norms of the actors involved, and the interactive scenes in which consent is negotiated. This analytical approach seeks to capture the nuanced, contextual, and relational nature of consent, transcend simplistic dichotomies, and recognize the intricate web of power, desire, and social norms inherent in intimate interactions.